Effect of Early Initiation of Evolocumab on Lipoprotein(a) in Patients with Acute Myocardial Infarction: Sub-Analysis of a Randomized Controlled Trial - Tomoaki Okada; Toru Miyoshi; Masayuki Doi; Kazumasa Nosaka; Ryu Tsushima; Satoko Ugawa; Wataru Takagi; Masahiro Sogo; Masahiko Takahashi; Hiroshi Ito (Journal of Cardiovascular Development and Disease, 2022)
Elevated circulating lipoprotein(a) levels are associated with an increased risk of cardiovascular events. We reported that early initiation of evolocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor, in addition to a statin substantially reduced the lipoprotein(a) levels in patients with acute myocardial infarction (AMI) after primary percutaneous coronary intervention (PCI). This sub-analysis sought to investigate the effect of evolocumab on lipoprotein(a) based on baseline lipoprotein(a) levels and characteristics. This study was a prespecified analysis of a randomized controlled trial that enrolled 102 patients who underwent primary PCI for AMI. Patients received pitavastatin (2 mg/day) alone or pitavastatin and evolocumab 140 mg subcutaneously within 24 h and 2 weeks after the index PCI. The evolocumab group showed significantly suppressed lipoprotein(a) levels in patients with baseline lipoprotein(a) levels of ≤10 mg/dL, 10 < lipoprotein(a) ≤ 20 mg/dL, and >20 mg/dL compared with the control group, as well as similar reductions in lipoprotein(a) levels in all patient subgroups. Among these subgroups, evolocumab tended to show more favorable effects in patients with diabetes mellitus. In AMI patients, early initiation of evolocumab therapy within 24 h of primary PCI suppressed the increase in lipoprotein(a) levels within 4 weeks, regardless of baseline levels and characteristics.